Analisis Sumber Dan Penggunaan Modal Kerja Terhadap Modal Kerja - Puspitasari, Ratih (STIE Kesatuan, 2009)
Sources and uses of funds is a report that presented by a company to determine changes in financial position for each period. A company manager has responsible of where the funds are obtained and how the funds are used.Each company involved in various investment activities and expenditures. When carrying out thoseactivities, the company produces the fund, the fund is defined as cash and cash equivalents and can also be interpreted as working capital. Working capital is defined as total current assets (gross working capital) or the difference between current assets and debt (net working capital). The purpose of this study was to analyze the working capital of the sources and uses of funds and analyze the level of corporate liquidity. The analysis was conducted to determine if activity of sources and uses of working capital and liquidity increase or decrease every period. The results showed that PT Indosat Tbk., And PT. XL Axiata, Tbk using aggressive strategies to manage their working capital, this is evidenced by the existence of a negatif working capital each year, and have fluctuating liquidity, so that from year to year has increased or decreased. However, when compared with the two companies PT. Indosat, Tbk is better than PT. XL Axiata, Tbk especially in the level of liquidity. The results of the evaluation in this study showed that reduction in working capital of PT Indosat Tbk. And PT. XL Axiata, Tbk, produces negatif number it is seen from the calculation of sources and uses, and also liquidity of PT. Indosat and PT. XL Axiata, Tbk increase and decrease every year. It is seen from the level of liquidity. From the results of these evaluations, the authors suggest in PT Indosat Tbk and PT. XL Axiata, Tbk to reduce current debts so that working capital generated can be increased, and collect the receivables was due to the existing cash in the company is not small, especially for PT. XL Axiata, Tbk.